Properties of large scale ultra-high temperature ceramic matrix composites made by filament winding and spark plasma sintering. (1st July 2021) - Sciti, D.; Galizia, P.; Reimer, T.; Schoberth, A.; Gutiérrez-Gonzalez, C.F.; Silvestroni, L.; Vinci, A.; Zoli, L.
Abstract: In this paper, for the first time, we report the manufacturing and characterization of large UHTCMCs discs, made of a ZrB2 /SiC matrix reinforced with PyC-coated PAN-based carbon fibres. This work was the result of a long term collaboration between different institutions and shows how it is possible to scale-up the production process of UHTCMCs for the fabrication of large components. 150 mm large discs were produced by filament winding and consolidated by spark plasma sintering and specimens were machined to test a large set of material properties at room and elevated temperature (up to 1800 °C). The extensive characterization revealed a new material with mechanical behaviour similar to CMCs, but with intrinsic higher thermal stability. Furthermore, the scale-up demonstrated in this work increases the appeal of UHTCMCs in sectors such as aerospace, where severe operating conditions limit the application of conventional materials.